Reconciling autistic individuals' self-reported social motivation with diminished social reward responsiveness in neuroimaging. (2019) - Yankowitz, Lisa D.; Clements, Caitlin C.
Abstract: The self-report of some autistic individuals that they experience social motivation should not be interpreted as a refutation of neuroimaging evidence supporting the social motivation hypothesis of autism. Neuroimaging evidence supports subtle differences in unconscious reward processing, which emerge at the group level and which may not be perceptible to individuals, but which may nonetheless impact an individual's behavior.